Direito tributário e modulação: a segurança jurídica no contexto da teoria dos sistemas de Niklas Luhmann - Barreni, Smith Robert (2022)
The work deals with modulation in tax matters in the perspective of the principle of legal certainty, based on Niklas Luhmann's systems theory. The main objective of the thesis is to verify when and how the Judiciary should modulate the effects of decisions that alter normative expectations stabilized in firm jurisprudence or binding precedent. After exposing the main theoretical aspects related to the Luhmannian model (concept and function of social systems, binary codes, programs, operational closure, cognitive opening, structural coupling), the research enters the scope of the process of implementing the law (which results in decisions judicial), moment in which the relationship of circularity between principles and rules, the role of dogmatics and the “systemic” concept of legal certainty are analyzed from Luhmann's view of trust, risk and danger. Further on, the central point of the research is reached, which comprises the verification of cases in which the effects of decisions on tax matters must be modulated, and how this must occur: by attributing ex nunc effects and/or tax regime transition. Finally, the work evaluates the consequences for the differentiation of the legal system of decisions that apply modulation from the selection of "consequentialist" arguments, more precisely those that involve damages to the public safes